Importance of internet resources in the biological education system - Grigoryeva, I.V.; Abukenova, V.S.; Gill, V.V. (Fundamental and Experimental Biology, 2018)
The article considers the possible use of Internet resources in the field of education, both in schools and in higher education. The importance of development of educational sites, scientific bases with open and free access to necessary literature and articles is considered. The important issue is that the introduction of websites should be smooth and understandable, without displacing paper carriers, which will be important and correct combination of both. Also, training with the help of the Internet gives tangible advantages in this area. Vari-ous educational sites provide many opportunities: from searching terminology, articles and books, to distance learning on the platforms of famous universities, using electronic libraries, the opportunity to communicate with world-famous lecturers, scientists, naturalists. In the article, we will look at each of the above possibilities on examples of Russian-language sites and not only, we will tell about their influence on the educational process, as an example, we will mention Karaganda State University. Let’s draw conclusions about whether innovation is really so important in the form of e-courses, online libraries, remote lectures and the creation of global open-source articles for educational institutions.